Dampak Struktur Kepemilikan, Proporsi Komisaris Independed, dan Komite Audit terhadap Earnings Management: Kualitas Audit sebagai Varabel Moderasi - Orie Secunda Ayunitantry; Fajri Adrianto (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2021)
This study aims to determine the effect of concentrated ownership structure, the proportion of independent commissioners and audit committees on earnings management with audit quality as a moderating variable in real estate and property sector companies listed on the IDX for the 2015-2019 period. Hypothesis testing is done by using panel data regression model fixed effect to a total of 110 observation data from 22 research samples. The results of hypothesis testing indicate that concentrated ownership and the proportion of independent commissioners doesn’t have a significant effect on earnings management, while the audit committee has a significant and negative effect on earnings management. The results also show that audit quality is able to moderate the negative effect of the audit committee on earnings management, meaning that the supervision of the Big 4 external auditors and the large number of audit committees will be able to improve the quality of financial reporting and reduce the company's earnings management actions.